From disciplinary enthusiasm to soulless tasks: norms behind computing educators' emotion display - Grande, Virginia; Kinnunen, Päivi; Barr, Matthew; Peters, Anne-Kathrin; Sabin, Mihaela; Sánchez-Peña, Matilde; Tshukudu, Ethel (European journal of engineering education, 2025)
Computing educators' emotion display is regulated by various norms and conventions. These (unwritten) rules affect which emotions educators feel comfortable expressing to different extents when students can perceive such displays. We draw on emotions and norms literature to investigate higher education computing educators' perceptions of what kinds of norms they have as criteria when considering which emotions they are (not) comfortable showing when teaching. Based on the qualitative content analysis of 22 interviews with computing educators from seven countries, we present various - sometimes connected or conflicting - norms that influence emotion display. These norms comprise moral, national, societal, professional, and affiliation norms that are salient in different ways for different educators. The findings contribute to a more nuanced understanding of various combinations of nested, context-dependent, and partly conflicting norms that guide educators' emotion display, an understanding of educators' work that goes beyond cognitive aspects.